다큐멘터리영화의 성공을 결정짓는 요인에 관한 비교사례연구 -<님아, 그 강을 건너지 마오>와 <두 개의 문>을 중심으로 - 임소연; 이윤철; Im, So-Yeon; Lee, Yun-Cheol (한국콘텐츠학회 논문지, 17(10), 2017)
After a few recent documentary films had commercial success, factors for their success are getting attention. This paper explores the factors of the financial success of two documentary films. "My Love, Don't Cross That River" gained extended popularity with its universal message, and "Two Doors" conveyed a poweful political message. This paper conducted a case study by inteviewing production directors and distribution managers. Analysis was based on the three categories suggested by Litman and Kohl(1989): creative sphere, distribution-scheduling release pattern, and marketing efforts. Findings present the common factors of the two movies' success in the following areas: persons and events showing a powerful reality, a message with new and fresh insight, artistic quality, distribution strategy with timely scheduling, release time (period), public relations, and advertising.. In addition, "My Love, Don't Cross That River" was helped by a sufficient budget for scheduling/releasing and advertising. Its wide-release stratergy worked as well. "Two Doors" was aided by the government support for release and by the special factor called 'Participating viewer'. By examining the factors of documentary films' commercial success, this study has an implication for the popularization of documentary movies by indicating how to strategically apply relevant factors. 최근 다큐멘터리 영화의 대중적 성공작들이 나타남에 따라 그 요인에 대한 관심이 대두되고 있다. 이에 본 연구는 보편적 메시지로 대중성을 확장한 <님아, 그 강을 건너지 마오>와 강한 정치적 메시지를 담은 <두 개의 문>의 사례를 통해 다큐멘터리 영화의 흥행요인을 규명하고자 했다. 이를 위해 Litman and Kohl(1989)이 제시한 영화 흥행요인 구분인 창조적 영역, 배급유통영역, 마케팅 영역을 기준으로 두 영화의 제작, 배급 담당자들의 인터뷰를 기반하여 사례분석을 이루었다. 분석결과, 강렬한 인물이나 사건 등의 실화 소재, 영화의 참신한 시선과 메시지, 영화적 완성도, 영화성격에 맞는 배급전략, 시의적 시기에 상영, 적절한 홍보, 광고 전략이 두 영화의 공통된 흥행요인임을 확인할 수 있었다. 이외에도 <님아, 그 강을 건너지 마오>는 민간투자로 인해 배급과 마케팅 비용이 풍부했던 점과 와이드릴리즈배급전략이 유효했고, <두 개의 문>은 정부의 개봉지원과 그리고 참여관객이라는 특수한 요인이 흥행에 영향을 미쳤음을 알 수 있었다. 이와 같이 본 연구는 다큐멘터리 영화의 흥행 요인을 규명하고, 이에 따른 전략적 작용에 대한 방안을 구체적으로 도출함으로써 다큐멘터리 영화의 대중화를 위한 시사점을 제시하고자 했다.